The Influence of Brand Awareness and Electronic Word of Mouth (E WOM), on Customer Trust in Decisions to Use Online Motorbike Taxi Services in Lamongan Regency - Kumalasari, Aprelia Nur (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Application-based online motorcycle taxi services are now increasingly popular with the general public. To be able to compete fiercely, companies are required to continue to innovate to satisfy existing customers and attract new customers. The aim of this research is to assess the level of Brand Awareness, Electronic Word of Mouth, and customer trust in the decision-making process for using Grab online services in Lamongan Regency. This research applies quantitative research using PLS SEM with a total of 255 Grab customers who live in the Lamongan City area. The findings of data analysis and hypothesis testing are : Brand Awareness has a significant influence on customer trust in users of the Grab online motorcycle taxi service in Lamongan district. Brand awareness has a significant influence on usage decisions. The findings of the hypothesis test analysis show There is a significant influence of the brand awareness variable on usage decisions among users of the Grab online motorcycle taxi service in Lamongan district. Electronic Word of Mouth has a significant influence on usage decisions. Hypothesis test analysis shows that there is a significant influence of the Electronic word of mouth variable on the decision to use the Grab online motorcycle taxi service in Lamongan Regency, Customer Trust has a Significant Influence on the Decision to Use Hypothesis test analysis 4 shows that there is a significant influence of the customer trust variable on the decision to use the Grab online motorcycle taxi service in the Regency Lamongan.